Prevalence and control of hypertension among diabetes patients in hospital universiti sains malaysia, malaysia - Salwa Selim Ibrahim; Ayman Selim I. Bougalambou; Fita Rahmawati; Mohamed Azmi Hassali; Syed Azhar Syed Sulaiman (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Hypertension in patients with type 2 diabetes mellitus is a prevalent condition that leads to substantial morbidity and mortality. The aim of the study was to determine the prevalence of hypertension in type 2 diabetes attending endocrinology clinics at Hospital Universiti Sains Malaysia (HUSM), to describe antihypertensive treatment patterns, and to evaluate the target of blood pressure achieved by antihypertensive agents. The study was a prospective follow-up descriptive study. Study conducted at diabetic clinic outpatient at HUSM, Kelantan, Malaysia from January to December 2007. A total of 1077 diabetic patients involve in this study. The findings of our study showed that the majority patients type 2 diabetes mellitus 998 (92.7 %) had hypertension. For the patients who were on antihypertensive medications, 254 (23.6 %) of them were on monotherapy and 311 (28.9 %), 179 (16.6 %), and 198 (18.4 %) respectively received two, three and more than three antihypertensive agents. The majority of patients 872 (87.4 %) were on angiotensin converting enzyme inhibitors/angiotensin receptor blockers either alone or in combination with other antihypertensive drugs. A number of 601 (55.8 %) patients achieved blood pressure targets ≤ 130/80 mm Hg. Almost all patients with hypertension anddiabetes will require a combination of antihypertensive medications. A number of patients was not achieved blood pressure goals ≤ 130/80 mm Hg. There is still need to educate both patients and health care providers of importance of achieving target of blood pressure in order to reduce morbidity and mortality in diabetes mellitus patients.Key words: Hypertension, type 2 diabetes mellitus, hypertension treatment